Blood Biochemical, Hormonal and Mineral Status of Cyclic, Acyclic, Endometriotic and Pregnant Crossbred Cows - Patel, Chirag I; Dhami, AJ; Panchal, MT; Sarvaiya, NP; Shah, SV (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
A study was carried out on infertile (acyclic and endometriotic) crossbred cows under field and normal cyclic (all 4 phases of cycle) as  well as pregnant (3, 6, 9 month) crossbred cows of University farm to evaluate the plasma progesterone (P4) and estradiol (E2) hormones  by RIA, and plasma total protein, cholesterol, calcium and phosphorus concentrations by using assay kits on chemistry analyzer. The  mean progesterone levels in cows during the diestrus phase and in pregnancy were significantly (p
Keywords: Blood biochemistry; Crossbred cattle; Cyclic; Acyclic; Pregnant; Endometritis